WHODUNNIT? An analysis of the sleuth in The murder at the Vicarage, by Agatha Christie, from the perspective of the crime fiction genre theory - Cesar, Álvaro (My University, 2021)
The objective of the present research is to analyze the distinct features of the book The murder at the vicarage by Agatha Christie to find the main characteristics of the genre, based on the theory of crime fiction. In order to understand the theory, it was traced the search of the main crime fiction literary works from late 19th to the beginning of 21st century and established the main characteristics of the crime fiction genre, which is the second chapter of the research. In the third chapter, it is proposed a historical study of Agatha Christie's main works and presentation of the main character Miss Marple. The forth chapter brings the analysis of the novel, seeking, in comparison to the theory, the distinct features of the book The murder at the vicarage by Agatha Christie in contrast to the characteristics of the crime fiction genre. [resumo fornecido pelo autor]
O objetivo da presente pesquisa é analisar as distintas características do livro O assassinato na casa do pastor de Agatha Christie para encontrar as principais características do gênero, com base na teoria da ficção policial. Para a compreensão da teoria, traçou-se a busca das principais obras literárias da ficção policial do final do século 19 ao início do século 21 e estabelecer as principais características do gênero da ficção policial, que é o segundo capítulo da pesquisa. No terceiro capítulo, é proposto um estudo histórico das principais obras de Agatha Christie e a apresentação da personagem principal Miss Marple. O quarto capítulo traz a análise do romance, buscando, em comparação com a teoria, as características distintas do livro O assassinato na casa do pastor de Agatha Christie em contraposição às características do gênero ficção policial. [resumo fornecido pelo autor]
Keywords: Ficção policial; Christie, Agatha, 1890-1976; Enigmas lógicos; Marple, Jane (Personagem fictício); Língua inglesa